PENDAMPINGAN DOSEN KEPADA TENAGA KEPENDIDIKAN UNMER PONOROGO SELAMA PPKM (PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT) DI MASA PANDEMI COVID-19 - Tutik Heriana; Sunarso, Maria Yosepin Endah Listyowati, Dendy Eta Mirlana, Mai Puspadyna Bilyastuti (Adiba Aisha Amira, 2022)
The campus world in responding to the COVID-19 pandemic storm is also not much different from other agencies, there are those who think that covid does exist, some think that covid is just a lie. Of course, it is a separate homework for the campus world, which consists of academics, lecturers and education staff, in color to face problems that can be said to be trials that are not easy, or not easy. The problem is that it has not been maximally socialized about the handling of prevention of health problems evenly and PPKM throughout the education staff of Unmer Ponorogo. In addition, the psychological and economic readiness of several education personnel with the storm of the covid pandemic, as well as employees who themselves and their families have been attacked by Covid-9 (Positive Covid 19). In this activity using the PAR (Participatory Action Research) method by being problem solving, providing socialization and engaging in direct assistance. The Pangabdi team from the Lecturer group at the Merdeka University, Ponorogo, realized that in dealing with the storm of the COVID- 19 pandemic, we had to work hand in hand with educational staff so that we could get through these difficult times together. Not only is it an obligation, but without the spirit of devotion that exists in the Tri Dharma of Higher Education, it is not necessarily the movement of this group of lecturers to apply elsewhere.